In Hot Water: The Failure of New Zealand’s Resource Management System to Respond to Events Induced by Climate Change - MacEwan, Jessie (Victoria University of Wellington Law Review, 2023)
The sustainable management of Aotearoa’s natural resources requires a system which is responsive to environmental changes. This will become more important in the future with the more frequent extreme environmental events predicted with climate change. The current system relies on statutory powers to review consents and adaptive management regimes to re-examine resource consents following environmental changes. This article focuses on two group consents to draw over 7,000,000 m3 of water per year from an aquifer in Northland. After these group consents were granted, a significant fire began which threatened the vulnerable wetland ecosystem. This article argues that the current system fails to respond to environmental events of this nature. With significant resource management reforms ongoing, it is crucial to consider how to create a responsive resource management system for a future dominated by the effects of climate change.